2015
DOI: 10.1002/pssb.201552345
|View full text |Cite
|
Sign up to set email alerts
|

Vacancy‐type defects and their annealing behaviors in Mg‐implanted GaN studied by a monoenergetic positron beam

Abstract: Vacancy-type defects in Mg-implanted GaN were probed using a monoenergetic positron beam. Mg ions of multiple energies (15-180 keV) were implanted to provide a 200-nmdeep box profile with Mg concentration of 4 Â 10 19 cm À3 . The major defect species of vacancies introduced by Mgimplantation was a complex between Ga-vacancy (V Ga ) and nitrogen vacancies (V N s). After annealing above 1000 8C, these defects started to agglomerate, and the major defect species became (V Ga ) 2 coupled with V N s. The defect rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
80
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 68 publications
(92 citation statements)
references
References 36 publications
10
80
2
Order By: Relevance
“…Because of the high kinetic energy of epithermal positrons, its annihilation characteristic is unlikely to be influenced by material properties. The observed behavior of S for p-type GaN has previously been reported, 34,36 and the decrease in the S s values can be attributed to the annihilation behavior of positrons at the surface of p-type GaN.…”
Section: Resultssupporting
confidence: 70%
See 2 more Smart Citations
“…Because of the high kinetic energy of epithermal positrons, its annihilation characteristic is unlikely to be influenced by material properties. The observed behavior of S for p-type GaN has previously been reported, 34,36 and the decrease in the S s values can be attributed to the annihilation behavior of positrons at the surface of p-type GaN.…”
Section: Resultssupporting
confidence: 70%
“…31,34 The localization of positrons near Mg atom at the N site (Mg Ga ) was also reported in Ref. 34. The present paper reports the result of the simulation for (Mg Ga ) 2 .…”
supporting
confidence: 74%
See 1 more Smart Citation
“…On the other hand, Ref. 10 reported that the V Ga (V N ) 2 complexes were detected by PAS for a sample after Mg implantation before annealing. However, since the dosage was sufficiently low in the present work, a probability of formation of a defect complex should have been low.…”
Section: -3mentioning
confidence: 99%
“…9 However, it has been reported that defects remain in the Mg-implanted GaN layer even after high-temperature annealing on the basis of positron annihilation spectroscopy (PAS) and photoluminescence (PL) studies. 10,11 To control the electrical properties of Mg-implanted GaN, an electrical measurement should be carried out to understand the thermal behavior of the defects by starting from a sample before high-temperature annealing for the activation of Mg acceptors. We here report measurement results of the electrical properties of a Mg-implanted GaN layer on a free-standing GaN substrate before high-temperature annealing.…”
mentioning
confidence: 99%